2022
DOI: 10.3390/ma15197016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Corrosion on the Bond Strength between Concrete and Rebar: A Systematic Review

Abstract: Corrosion of the reinforcement affects more than the cross-sectional area of the rebar. The volume of steel also increases due to expansive corrosion products, leading to the cracking, delamination, and spalling of concrete. As a result, the bond capacity between concrete and rebar is affected. Researchers have extensively examined the impact of corrosion on the bond strength between concrete and rebar to propose empirical, theoretical, or numerical predictive models. Therefore, research programs on this topic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 94 publications
1
4
0
Order By: Relevance
“…Interestingly, a better model was obtained by taking their ratio (C v /D o ). The transformation is consistent with previous work linking the C v /D o ratio to corrosion protection (Syll and Kanakubo, 2022).…”
Section: Model Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Interestingly, a better model was obtained by taking their ratio (C v /D o ). The transformation is consistent with previous work linking the C v /D o ratio to corrosion protection (Syll and Kanakubo, 2022).…”
Section: Model Resultssupporting
confidence: 92%
“…The present results, to the authors' knowledge, is the first to incorporate the specimen length in estimating the theoretical moment capacity, demonstrating the ability of the models to account for pitting or localized corrosion in naturally corroded beams. steel bars against progressive damage, improves the confinement, and consequently increases the bond strength of concrete (Syll and Kanakubo, 2022), thus reducing the impact of corrosion on the integrity of the RC beam. The variable was still included in the regression analysis because it may still contribute to the accuracy of C f once added with other predictors, particularly with bar diameter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the steel bar in prefabricated components is susceptible to corrosion during production, storage, transportation, and installation. This not only results in significant economic losses but also destroys the bonding surface with the subsequently poured concrete and undermines the interlocking interaction between the reinforcement and the concrete, thereby leading to potential implications on overall structural load-bearing capacity and performance of buildings [6][7][8]. Therefore, addressing the issue of steel bars corrosion in prefabricated construction is of significant importance.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Xia et al [ 14 ] found that the addition of natural pozzolans caused a decrease in the resistance to carbonation and a decrease in the diffusion coefficients of chlorides, parameters related to the corrosion of reinforced concrete, chloride being the main cause of reinforcement corrosion [ 44 , 45 ]. The corrosive process has arisen interest in the last decades because it has been identified as the main process related to the durability of reinforced concrete, which leads to great economic losses and, on the other hand, a huge environmental cost due to increased CO 2 emissions originated by the consumption of raw materials in the repair or replacement of damaged structures [ 46 , 47 ]. Although authors such as Kaid et al [ 48 ] and Fajardo et al [ 49 ] found that concrete mixed with natural pozzolan showed excellent corrosion resistance, quantification is necessary when these concretes are going to be used in areas with a high chloride content in the environment.…”
Section: Introductionmentioning
confidence: 99%